OPTIMALISASI FUNGSI PAPAN INDEKS STANDAR PENCEMAR UDARA (ISPU) OLEH DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU - Afrida Br Sianipar; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Air is an important component in human life. Air quality is a buffer of thesurvival of not only plants and animals but also humans so that the compositionneeds to be maintained but now the air quality has changed its composition due to airpollution so it can not support life. Air pollution is one of the many problems faced byurban areas as well as in Pekanbaru City. The Government issued a decision on thecalculation and reporting and information of the Air Pollution Standards Index(ISPU). ISPUs are reports of air quality to the public to explain how clean orcontaminated our air is and how it affects our health after breathing in the air forseveral hours or days.Based on the decision of Environmental Impact Management Agency (Bapedal)Number KEP-107 / Kabapedal / 11/1997, ISPU delivery to the public can be donethrough mass media and electronics and boards in public places. Pollutants orairborne pollutants are usually converted into one index value displayed on theseairborne stations can be either public awareness or public warning.The purpose of this research is to know how Optimizing Function Board AirPollution Standard Index (ISPU) by Environment and Sanitation Office of PekanbaruCity. This research was conducted by using qualitative research method, withdescriptive data assessment. In data collection, researchers used interviewtechniques, observation, literature study and documentation.The results of this study indicate that the Office of the Environment andSanitation of Pekanbaru City has issued a policy of procurement of Air PollutionStandards Index (ISPU). But the function of the Air Pollution Standards Index (ISPU)is still less than optimal. Factors affecting the function of the Air Pollution StandardsIndex (ISPU) are Human Resources, Coordination, Socialization and communityparticipationKeywords: Optimization, ISPU Function, Pekanbaru City